Engineering embolic microparticles from a periodically-pulsating charged liquid meniscus. (29th June 2018) - Tian, Xiaowei; Kong, Tiantian; Zhu, Pingan; Kang, Zhanxiao; Lei, Leyan; Tang, Xin; Wang, Liqiu
Highlights: Characterizing micro-dripping for effective fabrication of uniform microparticles. Correlating droplet size and controlling parameters. Correlating droplet-generation frequency and controlling parameters. Fabricating microparticles on a commercial scale for effective embolization. Abstract: A commercial-scale generation of uniform and well-controlled soft microparticles is critical for therapeutic embolization, a minimally invasive, nonsurgical interventional therapeutic technique for the treatment of various conditions, including tumors, vascular lesions and hemorrhages. We report the generation of required embolic microparticles from an electrified meniscus of the precursor alginate solution. A micro-dripping regime is identified with electric Bond number BE being from 0.3 to 1 and Weber number We < 1, where the conical tip of the charged meniscus emits a single yet fine droplet periodically. The droplet diameter dd and its generation frequency f scale with the dimensionless controlling parameters in the form of d d ∼ q 0.5, f ∼ q - 0.15 B E 0.67 in this regime, with q being the dimensionless flow rate. Our results are valuable for effective production of therapeutic microparticles on a commercial scale from precursor solution of similar physical properties.